The inflorescence in Commelinaceae - Panigo, Elisa (2011)
The structure of the synflorescence and the flowering unit (inflorescence) in Commelinaceae are characterized. The synflorescence is polytelic and the basic inflorescence type is a terminal pedunculate thyrse with an indeterminate central axis to which several to many cincinni are attached. Each thyrse is a florescence, and each cincinnus is a partial florescence. Variations mainly in the number of cincinni and in the number of flowers on each cincinnus determines the main differences found in the inflorescences of the different genera. Hypothesized developmental processes are described, with a view to finding relationships among different models characterized in the family as well as defining characters for cladistic studies, which may be useful to depict all the variations observedand serve as a guide for future phylogenetic studies.